Thermal properties of composite organic phase change materials (PCMs): A critical review on their engineering chemistry. (25th November 2020) - Atinafu, Dimberu G.; Ok, Yong Sik; Kua, Harn Wei; Kim, Sumin
Graphical abstract: Highlights: Challenges and mechanisms for engineering the thermal parameters of PCMs were summarized. Design techniques of novel composite PCMs were systematically analyzed. Recent advanced applications of composite PCMs were highlighted. Developing multifunctional composite PCMs is demanding for practical applications. Abstract: The design of composite phase change materials (PCMs) for thermal energy storage has attracted increasing attention owing to their high latent heat storage capability, enhanced thermal transfer performance, and low volume variation in addition to being seepage free. This review aims to provide techniques for engineering the thermal parameters of composite PCMs (e.g., latent heat, thermal conductivity, durability, and thermal stability) for several advanced large-scale applications and for producing desired thermophysical, chemical, and mechanical properties. In addition, approaches and materials employed for composite synthesis are described. Challenges and factors influencing the thermal energy storage performance of composite PCMs are also analyzed. Furthermore, the recent advanced applications of composite PCMs (including medical, building, electronics, solar, and energy storage and conversion) as well as the potential for producing energy storage and conversion materials are indicated. This report is likely to provide a foundation for designing multifunctional organic composite PCMs.